2022
DOI: 10.1007/s11356-022-21177-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fluorine removal performance and mechanism of spheroidal magnesium oxide before and after lanthanum modification

Abstract: Use simple magnesium salt as raw material, the magnesium oxide precursor powder was synthesized, and then the spheroidal magnesium oxide (SMO) was synthesized by controlled temperature calcination. Then lanthanum-modi ed spheroidal magnesium oxide (LSMO) was prepared by impregnation. The SMO and LSMO were characterized by X-ray diffraction (XRD), eld emission scanning electron microscopy (SEM), N 2 adsorption-desorption, infrared spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS). For the initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…There was an obvious peak at the wavelength of 3429 cm −1 , accompanied by adsorption peaks at 1470 cm −1 and 1098 cm −1 , which exhibited a characteristic O-H stretch band. It indicated that the material contained hydroxy groups [47]. By comparing the infrared spectra before and after adsorption, it was found that the peak strength of the hydroxyl group before adsorption was weaker than that after adsorption, in the range of 3200-3600 cm −1 .…”
Section: Adsorption Characterizationmentioning
confidence: 97%
“…There was an obvious peak at the wavelength of 3429 cm −1 , accompanied by adsorption peaks at 1470 cm −1 and 1098 cm −1 , which exhibited a characteristic O-H stretch band. It indicated that the material contained hydroxy groups [47]. By comparing the infrared spectra before and after adsorption, it was found that the peak strength of the hydroxyl group before adsorption was weaker than that after adsorption, in the range of 3200-3600 cm −1 .…”
Section: Adsorption Characterizationmentioning
confidence: 97%
“…Atoms such as O and F can generate hydrogen bonds. The stronger the hydrogen bond, the wider the tensile vibration band, and the higher the absorption intens [53,54].…”
Section: Ftir Analysismentioning
confidence: 99%